Concurrent presentation of systemic lupus erythematosus in mother and daughter - Pravesh Yadav; Anuja Yadav; Keemi Dalal; Ram Chander (Wolters Kluwer Medknow Publications, 2019)
Systemic lupus erythematosus (SLE) is a connective tissue disorder with a high prevalence in certain races like Africans. It also has a female predilection. The pathogenesis of SLE is a complex interplay of genetic and environmental factors. Familial presentation of SLE has been well documented. We herein illustrate a scenario of SLE presenting in related females (mother and daughter) concurrently with similar clinical features and fulfilling the Systemic Lupus Collaborating Clinics criteria. Stress was identified as a common possible triggering factor.